(untitled) (Jurnal Riset Agribisnis dan Peternakan, 2024)
Modified atmosphere is one of the preserves that is developing today. Modified atmosphere preservation is more effective at cold storage. This study aims to determine the Storage Period of Broiler Chicken Meat Packaged in a Modified Atmosphere with a CO2 content of 75% in cold temperatures. The material in this study is the meat of 24 broiler chickens. The treatment in this study was broiler chicken meat packaged in modified atmospheric packaging with a CO2 content of 75% stored in the refrigerator. The storage period is 3 weeks, namely day 0, day 7, day 14 and day 21. The parameters observed are physical quality and sensory quality. The results of the study showed that the longer the meat was stored in modified atmosphere packaging at cold temperatures, the physical quality, namely moisture content, pH, shrinkage, and cooking significantly increased. The longer the storage softness and ripening shrinkage decrease markedly. The longer the meat is stored in modified atmosphere packaging at cold temperatures, the more it decreases markedly on the sensory qualities of color, appearance and smell. The color is getting darker, the appearance is slimy and the smell is rotten. The conclusion is that the storage of meat in modified atmosphere packaging can extend the shelf life of meat.